Problematika Terkait Ketersediaan Sumber Daya Manusia Kesehatan Wilayah Kerja Puskesmas Di Provinsi Sumatera Utara - Ade Fitri Arianti; Tanjung, Nadya Ulfa; Susilawati, Susilawati (Jurnal Kesehatan Komunitas, 2024)
Health Human Resources is a subsystem in the National Health System that has a major role in the implementation of health achievement efforts. The availability and quality of adequate Health Human Resources are very influential in health development and health system management, so quality and quantity of human resource performance are needed. The purpose of this research is to find out the problems in the development of the availability of health human resources in the health sphere. The method used in this study is qualitative descriptive, using secondary data as a factual report to interpret the state of the object being studied. The results of the study show that the availability of human resources in the North Sumatra Health Center is not evenly distributed, this is seen from the distribution or recruitment of human resources that is still not optimal with the number of midwives (+10,910), nurses (+3,815), primary care doctors/doctors (+1,022) and pharmacists (+24) being classified as excess but the availability standards in each health center with three categories have not been met properly. It is necessary to have an analysis process that is more optimal in planning options according to the minimum standards of the Health Center so that the availability of Health Human Resources is responsible and balanced in the distribution rate. The current level of health human resources with curative efforts is more dominant in number with resources with promotive and preventive efforts because the production of health workers with these efforts is still low.